Spatial Behavior Of Informal Street Vendors In Formal Spaces: Case Study Of Tegallega Park, Bandung Indonesia - Irwan, Sudarisman (2024)
The bandung city government issued a policy allowing street vendors to conduct their activities in public spaces in 2011. The problem is that urban public spaces designed with a formal approach do not have a space to accommodate the informal activities of street vendors. Street vendors' space use causes issues. Knowing and understanding the needs of street vendors is crucial to designing a space that will facilitate their activities. Street vendors' activities in public spaces like city parks are still understudied, especially the relationship between park spaces and street vendor activities. This happens in bandung's tegallega park. This study examines the city government's regulations and actions on street vendors, other factors that affect street vendors' activities, and the impact of street vendors' activities on space and other park users in tegallega park. This study uses qualitative descriptive and behavioural mapping methods. Literature studies of regulatory documents and city government actions, mapping and documentation of activities and spaces, and visual observation of street vendors and other park users' behavior provided data. The results showed a relationship between the regulations and actions of the city government, the type of business and equipment used by street vendors, and the form, building elements, and materials of the space for street vendors’ activities. In addition, street vendors’ activity causes changes in the function and quality of space and the behaviour of other park users using various spaces.